Infrasound fluctuations during heavy fog event in the Arctic: A case study - Shumilov, Oleg I.; Kasatkina, Elena A.; Makarov, Dmitry V.; Krąpiec, Marek (Polish Polar Research, 2021)
Extremely dense fog event was studied on the 3rd December 2001, which occurred in the city of Apatity, the Kola Peninsula, northwestern Russia. Fog had low visibility (30–50 m) and lasted 17 h. Variations of atmospheric pressure and electric field before and during the fog event were measured. Multiple Taper Method (MTM) of spectral analysis has revealed pulsations of the atmospheric electric field in the frequency band of 0.007–0.05 Hz with a power-law turbulence spectrum. MTM and wavelet decomposition analysis results indicate the appearance of two types of atmospheric pressure oscillations under the fog conditions: low-frequency variations with periods of internal gravity waves and a substantial increase in pulsation intensity (more than an order of magnitude) in the high frequency (0.03–0.35 Hz) range. These results may help to improve the understanding of the microphysics of fog formation, development, and dissipation. High-frequency pulsations generation of atmospheric pressure under the fog conditions is also of interest because their period is close to the range of infrasonic oscillations, which can have negative consequences for human health.